CBIO-09. INTRATUMORAL HETEROGENEITY OF DIELECTRIC PROPERTIES IN GLIOBLASTOMA. (9th November 2020) - Proescholdt, Martin; Haj, Amer; Doenitz, Christian; Schmidt, Nils Ole; Bomzon, Zeev
Abstract: INTRODUCTION: Recently, tumor treating fields (TTFields) were established for the treatment of newly diagnosed glioblastoma (GBM). One of the most crucial parameters defining the treatment efficacy of TTFields is the electric field intensity, which depends on the dielectric properties of the tumor tissue. In this study we determined the dielectric properties of GBM by analyzing resected tissue following a fast acquisition protocol. To account for the intratumoral heterogeneity, different regions of the tumor were analyzed separately. METHODS: A cohort of 38 patients with newly diagnosed GBM were analyzed. Tissue probes were acquired from the vital tumor area and perinecrotic compartment. The tissue was measured immediately to avoid artifacts. A fragment was dissected from each tissue sample and was placed into a cylindrical cell with a known diameter. The impedance was recorded at frequencies 20Hz-1MHz using a software specifically developed for this study, which controls the LCR meter. The measured impedance was translated into dielectric properties of the sample (conductivity and relative permittivity) based on the parallel plate model, the recorded complex impedance and the geometry of the samples. Each tissue probe was fixed, and stained with H&E to visualize cellularity, luxol fast blue to analyze the myelinated fiber content and against factor VIII related antigen to assess tumor vascularity. RESULTS: We found significant differences between the conductivity and permittivity of tissue samples from each individual tumor (mean conductivity [S/m]: 0.302; range: 0.607 – 0.100; mean permittivity [Farad/m]: 3519.8; range: 11182.5 – 135.7). Consistently, the perinecrotic areas displayed lower conductivity values compared to the solid tumor compartments. Histological analysis revealed significantly higher cellularity and lower myelinated fiber content in tissue samples with high conductivity and permittivity. CONCLUSION: The dielectric properties of GBM show a high intratumoral heterogeneity which correlate to the extent of cellularity and myelin fiber content within the tissue.